Mouse strain and brain region‐specific expression of the glutaminyl cyclases QC and isoQC. (1st June 2014) - Höfling, Corinna; Indrischek, Henrike; Höpcke, Theodor; Waniek, Alexander; Cynis, Holger; Koch, Birgit; Schilling, Stephan; Morawski, Markus; Demuth, Hans‐Ulrich; Roßner, Steffen; Hartlage‐Rübsamen, Maike
Abstract: Glutaminyl cyclases (QCs) catalyze the formation of pyroglutamate (pGlu) from glutamine precursors at the N‐terminus of a number of peptide hormones, neuropeptides and chemokines. This post‐translational modification stabilizes these peptides, protects them from proteolytical degradation or is important for their biological activity. However, QC is also involved in a pathogenic pGlu modification of peptides accumulating in protein aggregation disorders such as Alzheimer's disease and familial Danish and familial British dementia. Its isoenzyme (isoQC) was shown to contribute to aspects of inflammation by pGlu‐modifying and thereby stabilizing the monocyte chemoattractant protein CCL2. For the generation of respective animal models and for pharmacological treatment studies the characterization of the mouse strain and brain region‐specific expression of QC and isoQC is indispensible. In order to address this issue, we used enzymatic activity assays and specific antibodies to detect both QC variants by immunohistochemistry in nine different mouse strains. Comparing different brain regions, the highest enzymatic QC/isoQC activity was detected in ventral brain, followed by cortex and hippocampus. Immunohistochemical stainings revealed that QC/isoQC activity in cortex mostly arises from isoQC expression. For most brain regions, the highest QC/isoQC activity was detected in C3H and FVB mice, whereas low QC/isoQC activity was present in CD1, SJL and C57 mice. Quantification of QC‐ and isoQC‐immunoreactive cells by unbiased stereology revealed a higher abundance of isoQC‐ than of QC‐immunoreactive neurons in Edinger–Westphal nucleus and in substantia nigra. In the locus coeruleus, however, there were comparable densities of QC‐ and of isoQC‐immunoreactive neurons. These observations are of considerable importance with regard to the selection of appropriate mouse strains for the study of QC/isoQC relevance in mouse models of neurodegeneration and neuroinflammation and for the testing of therapeutical interventions in these models.